EVALUASI KUALITAS SEMEN BEKU AKIBAT PERBEDAAN METODE LAMA EQUILIBRASI DAN LAMA PENURUNAN SUHU SELAMA PROSESING SEMEN - Melkianus L. Jadi; Max A. Supit; Damai Kusumaningrum; Andrijanto H. Angi (Politeknik Pertanian Negeri Kupang, 2008)
The research is experiment in laboratory with using semen from 3 Priangan rams. The experiment use completely Randomized Design (CRD) of 4 x 4 Faktorial with three Priangan rams as replications. The treatment are equilibration time as first faktor with level 1 hour, 2 hours, 3 hours, 4 hours, and freezing time as second faktor with level 4 minutes, 8 minutes, 12 minutes, and 16 minutes.The variable observed is sperm motility, sperm abnormality, sperm membrane intact and sperm macrodome intact after thawing. Data was analysis by Analysis of Variance and further analysis by Duncan’s Multiple Range Test (DMRT).The result of experiment show that treatment between 3 hours equilibration and 12 minutes freezing time are the best significantly influence (P 0>01) with significantly (P >0,05) with significantly interaction between two factors on sperm motility, sperm membrane intact and sperm macrodome intact after thawing but there is no interaction(P<0,05) for sperm abnormality after thawing.Keywords: Equilibration, freezing, frozen semen.